Case report: Presentations and cytokine profiles of inflammatory non-pulmonary COVID-19 and related diseases in children - Chao, Yen-Chun; Yang, Horng-Woei; Chang, Lung; Tseng, Chih-Wen; Fang, Li-Ching; Ho, Che-Sheng; Chi, Hsin; Yang, Kuender D. (Frontiers in Pediatrics, 2023)
The pandemic of COVID-19 has evolved to dynamic waves of different SARS-CoV-2 variants. In the beginning, children with COVID-19 presented pulmonary involvement with mild disease. In the later waves of COVID-19, life-threatening non-pulmonary inflammatory diseases such as 1) aseptic meningoencephalitis (ME), 2) acute necrotizing encephalopathies (ANE), and 3) multisystem inflammatory syndrome in children (MIS-C) occurred to children. To alert early recognition and prevention of the life-threatening non-pulmonary COVID-19, we described ME, ANE, and MIS-C cases in terms of clinical manifestation, cytokine profile, and follow-up consequences. Based on the immunopathogenesis and risk factors of non-pulmonary COVID-19, we delineated early diagnosis and treatment to reduce morbidity and mortality in children.